Large azaacenes: pyridine rings reacting like carbonyl groups - Engelhart, Jens U.; Lindner, Benjamin; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (Organic letters, 2012)
N,N′-Dihydropentaazapentacenes and -hexacenes displaying terminal pyridine rings are surprisingly easily oxidized by MnO2 into their corresponding pyridones.